Microbiomes From Biorepositories? 16S rRNA Bacterial Amplicon Sequencing of Archived and Contemporary Intestinal Samples of Wild Mammals (Eulipotyphla: Soricidae) - Greiman, Stephen E.; Cook, Joseph A.; Odom, Timothy; Cranmer, Katelyn; Liphardt, Schuyler W.; Menning, Damian M.; Sonsthagen, Sarah A.; Talbot, Sandra L. (Frontiers in Ecology and Evolution, 2020)
Interest in gut microbial community composition has exploded recently as a result of the increasing ability to characterize these organisms and a growing understanding of their role in host fitness. New technologies, such as next generation amplicon (16S rRNA) sequencing, have enabled identification of bacterial communities from samples of diverse origin (e.g., fecal, skin, genital, environmental, etc.). Relatively little work, however, has explored the feasibility of utilizing historical samples (e.g., museum archived samples) of varying age, quality, and preservation type. Because natural history collections span multiple decades, these biorepositories have the potential to provide fundamental historical baselines to measure and better understand biodiversity on a changing planet. Utilizing even a small proportion of museum specimens could provide a means of sampling past microbial communities, allowing for direct comparison to contemporary communities and more complete understanding of dynamic shifts through time. We examined the feasibility of obtaining 16S rRNA amplicon microbiome data from whole gastrointestinal tracts (GIs) of shrews of varying age and preservation method, including 5 freshly collected shrew GIs immediately fixed in liquid nitrogen (LN2), 10 ten-year old shrew GIs frozen at -20°C (whole animal), and 10 shrews of varying ages (4 from 1968, 1 from 1980, 1 from 2001, 1 from 2004, 1 from 2007, 1 from 2011 and 2 from 2013) fixed and stored whole in 70% ethanol. Not surprisingly, results of 16S rDNA amplicon sequencing reveal significantly different bacterial communities between different preservation techniques and age of samples. Ten-year old frozen samples had bacterial communities most similar to freshly collected (LN2) samples, while the bacterial communities of both were significantly different from the 70% ethanol preserved samples of various ages. Amongst those preserved in 70% ethanol, age of samples also influenced bacterial community composition. Additionally, we compare results of OTU based and ASV based analyses. Looking ahead, field collectors and museums should develop and adopt best practices related to frozen preservation to ensure adequate material for future microbiome investigations.